2000
DOI: 10.1177/152700250000100303
|View full text |Cite
|
Sign up to set email alerts
|

The Underrepresentation of French Canadians on English Canadian NHL Teams

Abstract: Using a comprehensive data set covering the entire modern era of the National Hockey League (NHL), this article finds evidence that French Canadians have been underrepresented on English Canadian NHL teams, relative to their representation on U.S.-based teams. This underrepresentation on English Canadian teams was found not only for French Canadian players but also for off-ice personnel such as general managers and coaches. None of the traditional arguments as to why French Canadians may face entry barriers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…While the draft is certainly not the only means by which teams acquire players, it is perhaps the most important means, since it is he mechanism by which all of the top young amateur players are allocated to NHL teams. Longley (2000) found that the tendency for English Canadian teams to draft fewer French Canadians is particularly prevalent in the lower rounds of the draft (after the 100th overall selection). A similar question to the one posed above can be examined.…”
Section: The Entry Draftmentioning
confidence: 97%
See 4 more Smart Citations
“…While the draft is certainly not the only means by which teams acquire players, it is perhaps the most important means, since it is he mechanism by which all of the top young amateur players are allocated to NHL teams. Longley (2000) found that the tendency for English Canadian teams to draft fewer French Canadians is particularly prevalent in the lower rounds of the draft (after the 100th overall selection). A similar question to the one posed above can be examined.…”
Section: The Entry Draftmentioning
confidence: 97%
“…Similarly, French Canadian coaches have been highly underrepresented on English Canadian teams relative to U.S. teams (Longley 2000). The past two decades have also seen a number of Americans rise to head coaching and GM positions in the NHL; the great majority of these Americans have been employed by U.S.-based teams.…”
Section: Possible Explanations For the Underrepresentationmentioning
confidence: 98%
See 3 more Smart Citations